Individual and non-differentiated library-information service to civil servants - Bayramov, Alamdar Gambar oghlu; Hasanova, Aysel Vaqif kyzy (Technium Social Sciences Journal, 2022)
In the article were studied, the methods of organizing the library-information service for civil servants. Each method was studied separately. Have been analyzed the electronic resources that provide information to civil servants and have been interpreted the methods and models of evaluating information sources